Situaciones didácticas de Brousseau y logro de aprendizaje en fracciones en estudiantes de secundaria de la Institución Educativa 60814 Negro Urco, distrito de Napo 2022 - Molina Gallardo, Julio Cesar (2023)
This study was carried out with the purpose of relating Brousseau’s didactic situations and the achievement of learning in fractions in secondary school students of educational institution 60814 of Negro Urco in the District of Napo. The question was: What is the relationship between Brousseau’s didactic situations and the achievement of learning in fractions in secondary school students of that educational institution? The design corresponds to the relational type, field study, cross-sectional, bivariate. The population and sample were made up of the 123 students enrolled in 2022. To collect data, a questionnaire and a performance test were validated by experts. The conclusion is that the student’s t-value = 10.662; p-value (bilateral significance) = 0.000, which rejects Ho and accepts Ha at a significance level of 5%, which shows that there is a statistically significant relationship between Brousseau’s didactic strategies and the achievement of learning in fractions in secondary school students of educational institution 60814 Negro Urco District of Napo 2022, and demonstrates the hypothesis proposed in the research.